Developing A Calibration Moel of Leaf Water Potensial Determination in Tomato Plants Using Nir Spectroscopy with Temperature Compensation - Diding Suhandy; Takahisa Matsuoka (Jurnal Keteknikan Pertanian, 2008)
In this study a calibration model with temperature compensation for leaf water potential (LWP) determination in tomato plants was successfully developed. A number of 150 tomato plants (Lycopersicon esculentum ev. Momotaro T-93) were used as samples. The plants were cultivated under same EC level (0.8 dSm-1) in Deep Flow Technique (OFT) using Wagner's pot. For each leaf, the uon-plant" six spectral acquisitions from six positions were conducted. The measuring condition for spectral acquisitions was 10 ms for scanning time and 50 scans for averaging. Immediately after the lion plant" spectral acquisition, leaf was cut and its LWP value was measured using the pressure chamber method. The Partial Least Squares (PLS) Regression was used to develop a calibration model. The result showed that the best calibration model with temperature compensation was identified for the original spectra in the wavelength range of 700-1040 nm. This calibration model had R2 =0.83, SEC =0.091 and SEP =0.120. This calibration model resulted in low SEP and bias for prediction ofLWP for samples having temperature 15, 25 and 35°C. This study has shown the superiority of using calibration model with temperature compensation to that without temperature compensation. This result opened the possibility ofusing NIR spectroscopy as a tool for nondestructive on-plant LWP determination on the field.    Keywords: calibration model, temperature compensation, leaf water potential, pressure chamber method, on-plant spectral acquisition, on-plant LWP determination    Diterima: 10 Mei 2007; Disetujui: 15 Agustus 2007